2000
DOI: 10.1093/nar/28.7.1535
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of the fragile X syndrome expanded sequence d(CGG)n by interspersed d(AGG) trinucleotides diminishes the formation and stability of d(CGG)n tetrahelical structures

Abstract: Fragile X syndrome is caused by expansion of a d(CGG) trinucleotide repeat sequence in the 5' untranslated region of the first exon of the FMR1 gene. Repeat expansion is thought to be instigated by formation of d(CGG)(n)secondary structures. Stable FMR1 d(CGG)(n)runs in normal individuals consist of 6-52 d(CGG) repeats that are interrupted every 9-11 triplets by a single d(AGG) trinucleotide. By contrast, individuals having fragile X syndrome premutation or full mutation present >54-200 or >200-2000 monotonous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…This can assist in locating hotbeds of microsatellite birth/death activity in individual human genomes and in the genomes of other species-which is of paramount significance, as microsatellite births/deaths are expected to influence mutagenesis of the flanking sequences (Webster and Hagberg 2007), to have functional implications when located within coding exons, and to modify expression levels when located in proximity of genes (e.g., Hammock and Young 2005). Moreover, our results are instrumental in assessing the probability of a locus to bear novel, potentially disease-causing microsatellites, and of a microsatellite to acquire interruptions leading to its death and thus to a stabilization of the locus (and thus possibly to reduction of disease manifestation [Weisman-Shomer et al 2000;Matsuura et al 2006]). …”
Section: Implications For the Microsatellite Life Cycle In Primate Gementioning
confidence: 89%
See 1 more Smart Citation
“…This can assist in locating hotbeds of microsatellite birth/death activity in individual human genomes and in the genomes of other species-which is of paramount significance, as microsatellite births/deaths are expected to influence mutagenesis of the flanking sequences (Webster and Hagberg 2007), to have functional implications when located within coding exons, and to modify expression levels when located in proximity of genes (e.g., Hammock and Young 2005). Moreover, our results are instrumental in assessing the probability of a locus to bear novel, potentially disease-causing microsatellites, and of a microsatellite to acquire interruptions leading to its death and thus to a stabilization of the locus (and thus possibly to reduction of disease manifestation [Weisman-Shomer et al 2000;Matsuura et al 2006]). …”
Section: Implications For the Microsatellite Life Cycle In Primate Gementioning
confidence: 89%
“…The relative frequency of these two mechanisms occurring genome-wide is presently unknown; the latter route has received greater attention, as interruptions of disease-causing microsatellite alleles can decrease severity or prevent disease manifestation (Weisman-Shomer et al 2000;Matsuura et al 2006). Experimentally, interruptions have been shown to affect microsatellite mutational behavior in a manner consistent with microsatellite death.…”
mentioning
confidence: 99%
“…Also, these long repeat tracks may cause repeat associated non-AUG (RAN) translation, leading to a toxic polygutamine or polyalanine products (43). Although we are not aware of any study on the influence of AGG interruptions on mitochondrial dysfunction, it is known that AGG interruptions change the secondary structure of premutation mRNA transcripts (44,45) lower Complex activities or both, citrate synthase activity was evaluated ( Figure 2C). While no differences were obtained in these outcomes between diagnostic groups' means, the incidence of activities < 95%CI was 57% and 75% for asymptomatic and FXTAS-affected carriers, respectively (χ 2 test p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…During the first 10 years, the estimated direct cost per year to the NHS in England and Wales is £0.7-0.2 million by active cascade screening and £14. [5][6][7][8][9].1 million by a programme of prenatal screening. The incremental cost per extra carrier detected (using current practice as the reference standard) is on average only £165 (range: £129-182) by active cascade screening and £7543 (range: £5316-14,636) by prenatal screening.…”
Section: Findings Of the Fxs Modelmentioning
confidence: 99%
“…Evidence indicated that the risk for PMs to expand may depend on the absence of stabilising adenine-guanine-guanine (AGG) repeats, which interrupt the CGG repeat region. 6 The PM may be defined differently in terms of cut-off values of CGG repeats size, and there is a 'grey zone' from 40 to 60 CGG repeats. The stability of 40-60 CGG repeats and their clinical importance are uncertain and controversial.…”
Section: Genetic Features Of Fxsmentioning
confidence: 99%